Therapeutic drug monitoring in children and adolescents: findings on fluoxetine from the TDM-VIGIL trial - Frey, Michael; Smigielski, Lukasz; Tini, Elvira; Fekete, Stefanie; Fleischhaker, Christian; Wewetzer, Christoph; Karwautz, Andreas; Correll, Christoph U.; Gerlach, Manfred; Taurines, Regina; Plener, Paul L.; Malzahn, Uwe; et al. (Pharmaceutics, 2023)
Fluoxetine is the recommended first-line antidepressant in many therapeutic guidelines for children and adolescents. However, little is known about the relationships between drug dose and serum level as well as the therapeutic serum reference range in this age group. Within a large naturalistic observational prospective multicenter clinical trial (“TDM-VIGIL”), a transdiagnostic sample of children and adolescents (n = 138; mean age, 15; range, 7-18 years; 24.6% males) was treated with fluoxetine (10-40 mg/day). Analyses of both the last timepoint and all timepoints (n = 292 observations), utilizing (multiple) linear regressions, linear mixed-effect models, and cumulative link (mixed) models, were used to test the associations between dose, serum concentration, outcome, and potential predictors. The receiver operating curve and first to third interquartile methods, respectively, were used to examine concentration cutoff and reference values for responders. A strong positive relationship was found between dose and serum concentration of fluoxetine and its metabolite. Higher body weight was associated with lower serum concentrations, and female sex was associated with lower therapeutic response. The preliminary reference ranges for the active moiety (fluoxetine+norfluoxetine) were 208-328 ng/mL (transdiagnostically) and 201.5-306 ng/mL (depression). Most patients showed marked (45.6%) or minimal (43.5%) improvements and reported no adverse effects (64.9%). This study demonstrated a clear linear dose-serum level relationship for fluoxetine in youth, with the identified reference range being within that established for adults.